Analisis Usaha Penggemukan Domba Di Peternakan Donba Enggar Pare Kabupaten Kediri - Maharani, Navita; Choirina, Vifi Nurul; Sevia, Jeni (Universitas Islam Kadiri, 2025)
Sheep are small ruminant livestock that have great potential to meet animal protein for humans. Goat and sheep agribusiness has great potential and prospects for the needs of sacrifice, aqiqah, and the lifestyle needs of the Indonesian people who like goat and lamb satay cuisine. Donba Enggar Pare Farm is a sheep farming business in Kediri Regency that has implemented an intensive and modern maintenance system. This phenomenon made researchers interested in analyzing the sheep farming business at Donba Enggar Pare Farm. The purpose of this study was to determine the income and feasibility value of the sheep farming business. This research was conducted from September to November 2024. This study uses a quantitative descriptive approach using Cost, Income, R/C Ratio and BEP (Break Event Point) analysis. Based on the results of the study, it is known that the total cost incurred in the sheep fattening business is Rp. 100,866,667, with the income obtained being Rp. 121,800,000. So that the income of the sheep fattening business at Donba Enggar farm is Rp 20,933,333 using an intensive maintenance system with a raised cage. The R/C Ratio value of the sheep fattening business is 1.21, this indicates that the sheep fattening business at Donba Enggar farm is feasible to run